Analysis and Experimental Study of Acceleration Model for Short Interval and Multiple Impact Equipment - Feiyin Li; Shaojie Ma (Shock and Vibration)
Short interval and continuous high-impact experiments have very significant engineering application values, and impact acceleration is a key performance index of these dynamic experiments. This paper aims at the shortcomings of the existing multiple high-impact equipment, designs a new type of multiple high-impact equipment based on the collision contact mode by multiple impact components, and studies the composition of acceleration in impact experiment. The research results indicate that it is unreasonable to analyze the impact acceleration only based on rigid body dynamics theory and ignore the effect of the stress wave loading during an impact experiment. On this basis, a line contact model is adopted to modify the equivalent damping coefficient and obtain a nonlinear spring damping contact force model based on the line contact, and then a rigid body acceleration model of the impact experiment is established. A stress wave acceleration model is also established based on the one-dimensional stress wave transfer theory of the tested specimen. The established acceleration model is verified by different corresponding impact experiments. At the same time, the collision contact process of the impact experiment is also simulated which is combined with the finite element method. The simulation results were fundamentally consistent with the experiments and a fact that proves the correctness of analysis and modeling. The research results not only provide theoretical support for the design and analysis of the impact equipment and a new idea to realize multiple high-impact loading but also provide a methodology to be applied to the analysis and modeling of acceleration for similar high-impact experiments.